Near Infrared Organic Semiconducting Materials for Bulk Heterojunction and Dye-Sensitized Solar Cells - Singh, Surya Prakash; Sharma, G. D. (Chemical record, 2014)
Dye sensitized solar cells (DSSCs) and bulk heterojunction (BHJ) solar cells have been the subject of intensive academic interest over the past two decades, and significant commercial effort has been directed towards this area with the vison of developing the next generation of low cost solar cells. Materials development has played a vital role in the dramatic improvement of both DSSC and BHJ solar cell performance in the recent years. Organic conjugated polymers and small molecules that absorb solar light in the visible and near infrared (NIR) regions represent a class of emering materials and show a great potential for the use of different optoelectronic devices such as DSSCs and BHJ solar cells. This account describes the emering class of near infrared (NIR) organic polymers and small molecules having donor and acceptors units, and explores their potential applications in the DSSCs and BHJ solar cells. Near‐infrared organic materials: Organic conjugated polymers and small molecules that absorb solar light in the visible and near‐infrared regions represents a class of emerging materials and show a great potential for the use of different optoelectronic devices such as DSSCs and BHJ solar cells. This review describes the emering class of near‐infrared organic polymers and small molecules having donor and acceptors units, and explores their potential applications in DSSCs and BHJ solar cells.